Charles I King and collector - Chiswell, Lucy; Munz, Niko; Shawe-Taylor, Desmond; Rumberg, Per 1975- (Royal Academy of Arts, 2018)
"During his reign, King Charles I (1600-1649) assembled one of Europe's most extraordinary art collections. Indeed, by the time of his death, it contained some 2,000 paintings and sculptures. 'Charles I: King and Collector' explores the origins of the collection, the way it was assembled and what it came to represent. Authoritative essays provide a revealing historical context for the formation of the King's taste. They analyse key areas of the collection, such as the Italian Renaissance, and how the paintings that Charles collected influenced the contemporary artists he commissioned. Following Charles's execution, his collection was sold. This book, which accompanies the exhibition, reunites its most important works in sumptuous detail. Featuring paintings by such masters as Van Dyck, Rubens and Raphael, this striking publication offers a unique insight into this fabled collection" --